If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 5 = 2(2x + -1) * 1 + -1(x + -3) Reorder the terms: 5 + 3x = 2(2x + -1) * 1 + -1(x + -3) Reorder the terms: 5 + 3x = 2(-1 + 2x) * 1 + -1(x + -3) Reorder the terms for easier multiplication: 5 + 3x = 2 * 1(-1 + 2x) + -1(x + -3) Multiply 2 * 1 5 + 3x = 2(-1 + 2x) + -1(x + -3) 5 + 3x = (-1 * 2 + 2x * 2) + -1(x + -3) 5 + 3x = (-2 + 4x) + -1(x + -3) Reorder the terms: 5 + 3x = -2 + 4x + -1(-3 + x) 5 + 3x = -2 + 4x + (-3 * -1 + x * -1) 5 + 3x = -2 + 4x + (3 + -1x) Reorder the terms: 5 + 3x = -2 + 3 + 4x + -1x Combine like terms: -2 + 3 = 1 5 + 3x = 1 + 4x + -1x Combine like terms: 4x + -1x = 3x 5 + 3x = 1 + 3x Add '-3x' to each side of the equation. 5 + 3x + -3x = 1 + 3x + -3x Combine like terms: 3x + -3x = 0 5 + 0 = 1 + 3x + -3x 5 = 1 + 3x + -3x Combine like terms: 3x + -3x = 0 5 = 1 + 0 5 = 1 Solving 5 = 1 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -3/5c-7=6 | | 227=142-u | | 18m+9=3(4m-9) | | (x-7)(4)=0 | | 23-x=275 | | -0.6c-7=6 | | 3-5x-7x=87 | | 14x-3=9x+5 | | 168=19-v | | 2+e=-2 | | ln(5x)+ln(10x)= | | 3(5x+3)=-5(5x-2) | | v+60=5v | | 3x+90=126 | | 6x=9y-6 | | 0.6(b-4)=-9 | | 8x-2y=41 | | 1.82= | | x(x+12)=(x-4)(x-4) | | ln(5x)+ln(10x)=4 | | 4-v=265 | | 6x+9y=65 | | Y-4+7y=24 | | -16=-4+4y | | y-7.2=9 | | 8x-(11x-9)=24-3x | | X-17=3Y-17 | | a+5=6a | | 75+2y=42 | | 3v=v+38 | | 40.00+19.25x=69.25+16.00x | | ln(7)+ln(x+3)=0 |